BAHAN AJAR BAHASA ARAB DENGAN PENDEKATAN PEMBELAJARAN KONSTRUKTIVISME (PENGEMBANGAN MODEL PADA MADRASAH TSANAWIYAH) - Akla, Akla (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2015)
ABSTRACTÂ This research deals with a model development of a constructive-based Arabic teaching materials in Islamic Junior High School (IJHS) of Metro city, Lampung. The population of this research was all seventh graders of state IJHSÂ of Metro in Batang Hari East Lampung regency academic year of 2012/2013. The population consisted of 250 students from seven classes. The samples of this research were taken randomly using the random table system. The result of the field try out shows that the Arabic teaching material developed in this research is valid. There is a significant difference in term of grade of the experimental class before and after the treatment. The value of t-table is 1.68 while the value of t-observed is 25.109; so t-observed is higher than t-table (25.109>1.68). Meanwhile, the value of t-observed within the control class is smaller than t-table (1.36 < 1.68). It shows that the means of the control class before and after the treatment using a non-developed model remain similar.Â Keywords: Arabic, teaching materials, a constructive-base.